The environmental impact of NATREF refinery storm water on the Taaibosch spruit - Ramotsehoa, Motsehoa Cynthia (Vaal University of Technology, 2012)
NATREF is the only inland refinery in South Africa and as such has unique water disposal challenges since it does not have the advantage of marine outlet like many other refineries. Most of its process streams are treated by the Sasol water treatment facility, leaving the concern of water that collects and drains off during rain fall events from the refinery site. Two sampling points were used during this study. Temperature and pH were measured in situ while bacterial counts and algal bioassays were performed in VUT laboratory. The area experienced a total of 485 mm of rain during the study period with 75 % thereof during spring and summer, there rest in autumn and winter receiving no rain. The average seasonal pH of the samples remained between 8 and 9.3 and this was found to fall within TWQR as well as being within normal range for natural waters. The temperature changes followed a typical summer/winter pattern, with Taaibosch Spruit showing greater variations from 10.95 ˚C in winter to 21.4 ˚C in summer due to its shallow nature. TDS, Nitrates & phosphates were all above the TWQR. Higher HPC & FC counts were observed during spring when rain storms began with Taaibosch Spruit had the higher of the two. As the rainfall continued into summer, the most of the bacterial counts decreased up to the lowest in winter. Higher than expected coliform counts (between 0 and 8 x 104) were observed, indicating a possible source of pollution which has to be studied. Chlorophyll a values ranged from 2.85 μg/L during spring to100 μg/L in winter indicating the potential for stimulation of the algae and possible algal blooms. The algal bioassays showed inhibition potential of the water during spring, summer and autumn with recovery by the winter. This meant that the storm water from NATREF does have a potential to cause chemical & biological pollution of the Taaibosch Spruit although the actual source of storm water pollution has to be properly studied.
M. Tech. (Department of Biosciences: Biotechnology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Storm water; Pollution; Water quality variables; Algal bioassays; Indicator organisms; Water analysis; Dissertations, Academic -- South Africa.; Water -- Pollution.; Mineral industries -- Environmental aspects.; Environmental impact analysis.